Systematic Review on Anti-Aging Health Care - Piwpong, Ratchanee (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 3 (2018): July-September 2018, 2018)
This systematic review analyzed characteristics of data and knowledge related to anti-aging health care. The samples were 71 studies, classified as 60 English and 11 Thai studies which were published from 2007 to 2016. The research instrument was validated by 3 experts . The results indicated that most of the sampling in the research studies was randomized controlled trial and descriptive research (32.39%), followed by quasi-experimental (21.13%), and systematic literature review research (9.86%), respectively. The methods of anti-aging health care and their outcomes could be categorised into 4 issues: 1) Behavior modification shuch as calorie restrictions, eating food with sirtuin and having regular exercise 2) selecting aesthetic treatments such as taking vitamins, supplements and hormones, botox injections and dermal fillers 3) using alternative medicine and complementary medicine such as massage, herbal medicine and acupuncture, and 4) stem cell transplants. Nursing roles in anti-aging health care include: 1) health promotion and disease prevention for anti-aging 2) caring for recipients who receive anti-aging medication or synthetic substances. This study suggests that health promotion and disease prevention is one way to provide anti-aging from the inside of the cell to the outside of the person and live a healthy life. Keywords : Anti-Aging, Health Care for Anti-Aging, Systematic Review